Somalia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Somalia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights the Government of Somalia's continued significant efforts toward restoring its key economic and financial institutions despite a very difficult political environment. The Somali economy is expected to continue to be sustained by donor grants, remittances, and foreign direct investment, mostly by the Somali diaspora. Economic activity is projected to decelerate in 2016-17. Growth is projected to be 3.4 percent and 2.5 percent in 2016 and 2017, respectively. The Somali government will continue to implement measures to improve the fiscal framework, raise tax revenue, and implement structural reforms.